New Management Model of Modern Russian Economy: Regional Aspect - Nosova, Svetlana S.; Mackulyak, Ivan D.; Lyubimtseva, Svetlana V.; Askerov, Pulat F.; Shkalaberda, Leonid I.; Aliev, Ul’vi Takhirogly (International Review of Management and Marketing, 2016)
Theoretic-methodological bases for the research of innovative development of the Russian economy. Proved the need to find effective approaches to scientific development and practical implementation of the concept of strategic management. Asked to abandon the current model for managing commodity economies and ensure transition to innovation model of economic development of Russia as a result of a major change in strategy, the objectives and the means of economic policy, which would provide domestic and external problems. The main trend of the new model must be in high technology management, production and dissemination of knowledge, which provides a mechanism for the effective growth of industry clusters. Stressed that the current economic development outside the institutional changes cannot develop fully, or might, but in an imperfect form. It is revealed that the institutions cooperating with the production and penetrates into it, provide the dynamism of economic management. The necessity of interaction between science, business and Government from a position of selecting priority areas for regional development in terms of national development with the aim of identifying determinants of the competitive advantages of the Russian economy to ensure economic growth through the development of a cluster of regional sector of the Russian economy. Keywords: economic policy, priorities of economic policy, the model of economic management of raw materials, non-oil sector, innovative model of management of the economy, the multiplier effect, development institutions, regional economy, cluster arrangement of Russian territories JEL Classifications: O18, P25, R11, R58